A silicon-carbon composite material with a one-shell multi-core structure and rich internal voids, and a preparation method and application thereof

By preparing silicon carbon composite materials with a shell multi-core structure and internally rich in voids, the problems of volume expansion and SEI film consumption during the lithiation of lithium-ion battery materials are solved, and higher cycle stability and specific capacity are achieved.

CN119750583APending Publication Date: 2025-04-04SHENZHEN JINTANG NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411984187.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The volume expansion of existing silicon-based lithium-ion battery materials during lithiation leads to structural pulverization, and the unstable solid electrolyte mesophase (SEI) film consumes lithium ions, limiting its application.

Method used

A silicon carbon composite material with a shell multi-core structure and internally rich in voids is used, which is prepared by ball milling, mixing, spray injection and pickling, and the carbon shell and internal voids are used to relieve volume expansion and stress.

Benefits of technology

The cycle stability and specific capacity of the negative electrode material of lithium-ion battery is significantly improved, and the charging and discharging efficiency is achieved, and the preparation process is simplified and the cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119750583A_ABST
    Figure CN119750583A_ABST
Patent Text Reader

Abstract

The present invention discloses a silicon-carbon composite material having a one-shell multi-core structure and rich in voids, and a preparation method and application thereof. The preparation method comprises the following steps: S1, fully ball-milling photovoltaic silicon waste to obtain a silicon source material for standby use; S2, uniformly mixing the silicon source material with a liquid carbon source to obtain a silicon-containing mixed liquid for standby use; S3, injecting the silicon-containing mixed liquid into a reactor pre-heated to a target pyrolysis temperature to obtain precursor carbon-coated silicon particles; S4, acid-washing the precursor carbon-coated silicon particles to obtain a silicon-carbon composite material having a one-shell multi-core structure and rich in voids. The silicon-carbon composite material in the present invention, due to its unique one-shell multi-core structure and rich in voids, can provide a higher capacity and maintain good cycle stability when used as a negative electrode material for lithium-ion batteries; this structure effectively alleviates the volume expansion of the silicon core during the charge and discharge process, thereby extending the service life of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a silicon-carbon composite material having a one-shell multi-core structure and rich internal voids, and a preparation method and application thereof. Background Art

[0002] Silicon materials are considered to be the most promising negative electrode materials for the new generation of lithium-ion batteries due to their ultra-high theoretical specific capacity and suitable operating voltage. They are expected to significantly improve the energy density of batteries and meet the needs of the rapid development of power batteries. However, silicon materials undergo severe volume expansion during the lithiation process, resulting in the pulverization of the material structure. At the same time, the unstable solid electrolyte interphase (SEI) film formed consumes a large amount of lithium ions, thus limiting their direct application. To solve these problems, researchers have promoted the development of silicon-based materials by regulating the size, morphology and composite structure of silicon materials. Among them, preparing nano-silicon and combining it with carbon materials has become an effective strategy. On the one hand, nano-sizing can significantly reduce the negative impact of the volume effect of silicon; on the other hand, carbon materials have high mechanical strength and excellent conductivity. Combining with silicon can not only alleviate volume expansion, but also improve the conductivity of composite materials.

[0003] Although the solid-core-shell-carbon-coated silicon structure has a certain effect in improving the electrochemical performance of silicon-based materials, its long-term cycling performance is still limited by the failure of the carbon coating structure caused by the volume expansion / contraction of the silicon core. Therefore, introducing internal voids into the core-shell structure has become a key strategy to improve the electrochemical performance of silicon-carbon composites. This unique structure accommodates the volume changes of silicon by reserving voids, significantly alleviating the stress and volume effects generated during the lithiation / delithiation process, thereby effectively reducing the impact of electrode volume expansion. However, the existing methods for preparing silicon-carbon core-shell structures with internal voids usually require complex template introduction steps [Mi H et al, A self-sacrifice template strategy to fabricate yolk-shell structured silicon@void@carbon composites for high-performance lithium-ion batteries. Chemical Engineering Journal, 2018, 351: 103-109; Kim JS, et al. Three-dimensional silicon / carbon core–shell electrode as an anodematerial for lithium-ion batteries. Journal of Power Sources, 2015, 279: 13-20; Xue H et al. Unraveling the New Role of Metal-Organic Frameworks in Designing Silicon Hollow Nanocages for High-Energy Lithium-Ion Batteries. ACS Applied Materials & Interfaces, 2021, 13(34): 40471-40480], which increases the difficulty of preparation and the high cost, limiting its promotion in practical applications. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present disclosure provides a silicon-carbon composite material having a one-shell multi-core structure and rich internal voids, and a preparation method and application thereof. The preparation method is simple, and the prepared material has high capacity and good cycle stability when used as a negative electrode material for lithium-ion batteries.

[0005] The present invention adopts the following technical solution:

[0006] A method for preparing a silicon-carbon composite material having a one-shell multi-core structure and rich in voids, comprising the following steps:

[0007] S1. Fully ball-mill the photovoltaic silicon waste to obtain silicon source material for standby use;

[0008] S2, uniformly mixing the silicon source material and the liquid carbon source to obtain a silicon-containing mixed liquid for standby use;

[0009] S3, injecting the silicon-containing mixed liquid into a reaction furnace that has been preheated to a target pyrolysis temperature to obtain precursor carbon-coated silicon particles;

[0010] S4. The precursor carbon-coated silicon particles are acid-washed to obtain a silicon-carbon composite material having a one-shell multi-core structure and rich in voids.

[0011] The photovoltaic silicon waste described in step S1 is a polycrystalline structure, and the high-density grain boundaries inside it are active areas in the silicon.

[0012] The size of the silicon source material obtained after ball milling in step S1 is less than or equal to 300 nm. The smaller the size of the silicon particles, the smaller the absolute volume change of the electrode sheet after lithium insertion, and the more it can maintain the inherent morphological structure and cycle stability.

[0013] Preferably, the size of the silicon source material obtained after ball milling is 50-150 nm.

[0014] The liquid carbon source in step S2 is one or more of pyridine, pyrrole, cyclohexane, N-methylpyrrolidone, n-heptane, toluene, aniline and washing oil.

[0015] Preferably, the liquid carbon source is a combination of one or more of pyridine, toluene and wash oil.

[0016] The mass / volume ratio of the silicon source material to the liquid carbon source in step S2 is 1:(0.5-50).

[0017] Preferably, the mass / volume ratio of the silicon source material to the liquid carbon source is 1:(1-20).

[0018] The target pyrolysis temperature in step S3 is based on the principle that the carbon source can be vapor deposited. Depending on the carbon source and the ratio, the temperature range is 800-1200°C, and the pyrolysis time is 5-120 minutes. A longer insulation time can make the carbon layer grow as regularly as possible, but it is limited by the pyrolysis temperature.

[0019] Preferably, the pyrolysis time is 10-60 min.

[0020] In step S3, the silicon-containing mixed liquid is injected into the pyrolysis reactor by spraying, injection, or dripping.

[0021] Preferably, the silicon-containing mixed liquid is injected into the pyrolysis reactor by spraying. The spraying method can make the raw materials heated more evenly and over a larger heating area after entering the reactor, thereby increasing the degree of gas phase pyrolysis.

[0022] The acid solution used in the pickling process in step S4 is a hydrofluoric acid solution with a volume fraction of 5%-20%. The hydrofluoric acid is used to selectively etch the oxidized components of silicon in the silicon-carbon precursor, thereby introducing a large number of voids inside the core-shell structure.

[0023] The duration of the pickling process in step S4 is 1-5 hours, and the pickling time is affected by the concentration of hydrofluoric acid and the proportion of oxidizing components.

[0024] A silicon-carbon composite material having a one-shell multi-core structure and rich in voids obtained according to the preparation method.

[0025] An application of the silicon-carbon composite material having a one-shell multi-core structure and rich internal voids obtained according to the preparation method as a negative electrode material for a lithium-ion battery.

[0026] The technical solution of the present invention has the following advantages:

[0027] A. The silicon-carbon composite material in the present invention has a one-shell multi-core structure and is rich in voids. On the one hand, the carbon shell can improve the conductivity of the silicon negative electrode material, improve the SEI film formation of the silicon-based negative electrode, and alleviate the volume expansion of the silicon core; on the other hand, the rich internal voids in the carbon shell reserve space for the volume expansion of the silicon core, which is conducive to maintaining the stability of the electrode structure. When used as a negative electrode material for lithium-ion batteries, it has stable cycle performance and can achieve higher specific capacity and charge and discharge efficiency.

[0028] B. The present invention provides a simple and efficient preparation method, which can mass-produce silicon-carbon composite materials with excellent performance through the steps of ball milling, mixing, spray injection and pickling. This method not only simplifies the production process, but also improves the production efficiency and quality of the material.

[0029] C. In recent years, the photovoltaic industry has achieved rapid development, and it is estimated that the total installed capacity of global photovoltaic equipment will reach 650GW in 2030. The photovoltaic industry relies on silicon-based solar cells as the main energy medium. In the process of rapid development of the industry, a large amount of photovoltaic silicon processing waste is inevitably generated. The present invention uses photovoltaic silicon waste as raw material to achieve waste recycling, which not only reduces production costs, but also complies with the concept of environmental protection and sustainable development. At the same time, through the optimization of technical solutions, such as the use of a specific liquid carbon source and a suitable pyrolysis temperature, the performance and environmental protection of the material are further improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the specific embodiments of the present invention, the drawings required for use in the specific embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0031] Figure 1 This is a transmission electron microscope image of the silicon-carbon composite material obtained in Example 1 (I);

[0032] Figure 2 This is a transmission electron microscope image (II) of the silicon-carbon composite material obtained in Example 1;

[0033] Figure 3 is a transmission electron microscope image of the silicon-carbon composite material obtained in the comparative example;

[0034] Figure 4 The figure is a comparison chart of the cycle performance of the silicon-carbon composite material obtained in Example 1 and the comparative example. DETAILED DESCRIPTION

[0035] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Example 1

[0037] This embodiment provides a silicon-carbon composite material, and the preparation method thereof comprises the following steps:

[0038] S1. The photovoltaic silicon waste is fully ball-milled to an average diameter of 300 nm to obtain a silicon source material for standby use;

[0039] S2, weigh 0.5 g of the silicon source material obtained after ball milling, add 3 mL of pyridine, mix thoroughly and evenly to obtain a silicon-containing mixed solution for standby use;

[0040] S3, spraying the silicon-containing mixed liquid into a pyrolysis reaction furnace preheated to 900° C., with a nitrogen atmosphere in the furnace, and keeping the temperature for 60 minutes to obtain precursor carbon-coated silicon particles;

[0041] S4. The precursor carbon-coated silicon particles are washed with hydrofluoric acid at a hydrofluoric acid concentration of 10% for 2 hours, followed by filtration and drying to obtain the desired silicon-carbon composite material.

[0042] Example 2

[0043] This embodiment provides a method for preparing a silicon-carbon composite material, which is different from Embodiment 1 in that in step S1, the average particle size of photovoltaic silicon waste is reduced to 100 nm by ball milling.

[0044] Example 3

[0045] This embodiment provides a silicon-carbon composite material, and the preparation method thereof comprises the following steps:

[0046] S1. The photovoltaic silicon waste is fully ball-milled to an average diameter of 300 nm to obtain a silicon source material for standby use;

[0047] S2, weigh 0.5g of the silicon source material obtained after ball milling, add 0.5mL of washing oil, mix thoroughly and evenly to obtain a silicon-containing mixed solution for standby use;

[0048] S3, spraying the silicon-containing mixed liquid into a pyrolysis reaction furnace preheated to 800° C., with a nitrogen atmosphere in the furnace, and keeping the temperature for 120 minutes to obtain precursor carbon-coated silicon particles;

[0049] S4. The precursor carbon-coated silicon particles are washed with hydrofluoric acid at a hydrofluoric acid concentration of 10% for 2 hours, followed by filtration and drying to obtain the final silicon-carbon composite material.

[0050] Example 4

[0051] This embodiment provides a method for preparing a silicon-carbon composite material, which is different from Embodiment 1 in that the mass / volume ratio of the silicon source material to the liquid carbon source in step S2 is 1:20, that is, 10 ml of pyridine is added.

[0052] Example 5

[0053] This embodiment provides a method for preparing a silicon-carbon composite material, which is different from Embodiment 1 in that the pyrolysis temperature in step S3 is 1100° C. and the holding time is 60 min.

[0054] Example 6

[0055] This embodiment provides a method for preparing a silicon-carbon composite material, which is different from Embodiment 1 in that the concentration of hydrofluoric acid used in step S4 is 10%, and the pickling time is 4 hours.

[0056] Example 7

[0057] This embodiment provides a silicon-carbon composite material, and the preparation method thereof comprises the following steps:

[0058] S1. The photovoltaic silicon waste is fully ball-milled to an average diameter of 50 nm to obtain a silicon source material for standby use;

[0059] S2, weigh 0.5 g of the silicon source material obtained after ball milling, add 25 mL of pyridine, mix thoroughly and evenly to obtain a silicon-containing mixed solution for standby use;

[0060] S3, spraying the silicon-containing mixed liquid into a pyrolysis reaction furnace preheated to 1200° C., with a nitrogen atmosphere in the furnace, and keeping the temperature for 5 minutes to obtain precursor carbon-coated silicon particles;

[0061] S4. The precursor carbon-coated silicon particles are washed with hydrofluoric acid at a hydrofluoric acid concentration of 5% for 5 hours, followed by filtration and drying to obtain the desired silicon-carbon composite material.

[0062] Example 8

[0063] This embodiment provides a silicon-carbon composite material, and the preparation method thereof comprises the following steps:

[0064] S1. The photovoltaic silicon waste is fully ball-milled to an average diameter of 150 nm to obtain a silicon source material for standby use;

[0065] S2, weigh 0.5 g of the silicon source material obtained after ball milling, add 0.25 mL of pyridine, mix thoroughly and evenly to obtain a silicon-containing mixed solution for standby use;

[0066] S3, spraying the silicon-containing mixed liquid into a pyrolysis reaction furnace preheated to 1000° C., with a nitrogen atmosphere in the furnace, and keeping the temperature for 10 minutes to obtain precursor carbon-coated silicon particles;

[0067] S4. The precursor carbon-coated silicon particles are washed with hydrofluoric acid, the concentration of the hydrofluoric acid used is 20%, and the washing time is 1 hour. Then, the desired silicon-carbon composite material is obtained by suction filtration and drying.

[0068] Comparative Example 1

[0069] This comparative example provides a silicon-carbon negative electrode material, and the preparation method thereof comprises the following steps:

[0070] S1. The photovoltaic silicon waste is fully ball-milled to an average diameter of 300 nm to obtain a silicon source material for standby use;

[0071] S2, weigh 0.5 g of the silicon source material obtained after ball milling, add 3 mL of pyridine, mix thoroughly and evenly to obtain a silicon-containing mixed solution for standby use;

[0072] S3, spraying the silicon-containing mixed liquid into a pyrolysis reaction furnace preheated to 900° C., wherein the furnace is filled with a nitrogen atmosphere, and the temperature is maintained for 60 minutes to obtain a silicon-carbon composite material.

[0073] Performance measurement:

[0074] The examples 1-6 and comparative example 1 were used as negative electrodes of lithium-ion batteries to assemble button batteries.

[0075] The specific method is as follows: the silicon-carbon composite material obtained in the embodiment and the comparative example, sodium carboxymethyl cellulose, acetylene black, and single-walled carbon nanotube aqueous slurry are mixed in a mass ratio of 91:6:2:1 to prepare an electrode slurry, and the slurry is evenly coated on a carbon-coated copper foil to prepare an electrode sheet. The lithium sheet is used as a counter electrode to assemble a half-cell, and the charge and discharge performance is tested at a current density of 500 mA / g in a LAND (CT3001A) battery test system.

[0076] Table 1 Battery performance test table

[0077]

[0078]

[0079] Figure 1-Figure 3 By comparison, it can be clearly found that the silicon-carbon composite material prepared by the present application scheme has a one-shell multi-core structure and is rich in voids. Figure 4 As shown, the introduction of voids in the core-shell structure can significantly improve the electrochemical performance of the silicon-carbon composite material. The initial reversible specific capacity of Example 1 is 1196 mAh / g, and the specific capacity remains at 1158 mAh / g after 200 cycles, with a corresponding capacity retention rate of up to 96.8%. The capacity retention rate of the silicon-carbon precursor (Comparative Example 1) without the introduction of voids is 87.3%. Although the introduction of voids in the core-shell structure will lose some capacity (due to the reduction in silicon content), the rich voids have limited relief of the volume expansion effect of silicon, giving the silicon-carbon composite material better electrochemical performance and structural stability.

[0080] The silicon-carbon composite material in the present invention has a one-shell multi-core structure and is rich in voids. On the one hand, the carbon shell can improve the conductivity of the silicon negative electrode material, improve the SEI film formation of the silicon-based negative electrode, and alleviate the volume expansion of the silicon core; on the other hand, the rich internal voids in the carbon shell reserve space for the volume expansion of the silicon core, which is conducive to maintaining the stability of the electrode structure. When used as a negative electrode material for lithium-ion batteries, it has stable cycle performance and can achieve higher specific capacity and charge and discharge efficiency.

[0081] The present invention provides a simple and efficient preparation method, which can mass-produce silicon-carbon composite materials with excellent performance through the steps of ball milling, mixing, spray injection and pickling. This method not only simplifies the production process, but also improves the production efficiency and quality of the material.

[0082] In recent years, the photovoltaic industry has achieved rapid development, and it is estimated that the total installed capacity of global photovoltaic equipment will reach 650GW in 2030. The photovoltaic industry relies on silicon-based solar cells as the main energy medium. In the process of rapid development of the industry, a large amount of photovoltaic silicon processing waste is inevitably generated. The present invention uses photovoltaic silicon waste as raw material to achieve waste recycling, which not only reduces production costs, but also complies with the concept of environmental protection and sustainable development. At the same time, through the optimization of technical solutions, such as the use of a specific liquid carbon source and a suitable pyrolysis temperature, the performance and environmental protection of the material are further improved.

[0083] Any matters not described in the present invention are applicable to the prior art.

[0084] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the present invention.

Claims

1. A method for preparing a silicon-carbon composite material having a one-shell multi-core structure and rich in voids, characterized in that: The steps include: S1. Fully ball-mill the photovoltaic silicon waste to obtain silicon source material for standby use; S2, uniformly mixing the silicon source material and the liquid carbon source to obtain a silicon-containing mixed liquid for standby use; S3, injecting the silicon-containing mixed liquid into a reaction furnace that has been preheated to a target pyrolysis temperature to obtain precursor carbon-coated silicon particles; S4. The precursor carbon-coated silicon particles are acid-washed to obtain a silicon-carbon composite material having a one-shell multi-core structure and rich in voids.

2. The method for preparing the silicon-carbon composite material having a one-shell multi-core structure and rich internal voids according to claim 1, characterized in that: The photovoltaic silicon waste described in step S1 is of a polycrystalline structure.

3. The method for preparing the silicon-carbon composite material having a one-shell multi-core structure and rich internal voids according to claim 1, characterized in that: The size of the silicon source material obtained after ball milling in step S1 is less than or equal to 300 nm.

4. The method for preparing the silicon-carbon composite material having a one-shell multi-core structure and rich internal voids according to claim 1, characterized in that: The liquid carbon source in step S2 is one or more of pyridine, pyrrole, cyclohexane, N-methylpyrrolidone, n-heptane, toluene, aniline and washing oil.

5. The method for preparing the silicon-carbon composite material having a one-shell multi-core structure and rich internal voids according to claim 1, characterized in that: The mass / volume ratio of the silicon source material to the liquid carbon source in step S2 is 1:(0.5-50).

6. The method for preparing the silicon-carbon composite material having a one-shell multi-core structure and rich internal voids according to claim 1, characterized in that: In step S3, the target pyrolysis temperature is 800-1200° C., and the pyrolysis time is 5-120 min.

7. The method for preparing the silicon-carbon composite material having a one-shell multi-core structure and rich internal voids according to claim 1, characterized in that: In step S3, the silicon-containing mixed liquid is injected into the pyrolysis reactor by spraying, injection, or dripping.

8. The method for preparing a silicon-carbon composite material having a one-shell multi-core structure and rich in voids according to claim 1, wherein the acid solution used in the pickling process in step S4 is a hydrofluoric acid solution with a volume fraction of 5%-20%; The duration of the pickling process in step S4 is 1-5 hours.

9. A silicon-carbon composite material having a one-shell multi-core structure and rich internal voids obtained by the preparation method according to any one of claims 1 to 8.

10. Use of a silicon-carbon composite material having a one-shell multi-core structure and rich internal voids obtained by the preparation method according to any one of claims 1 to 8 as a negative electrode material for a lithium-ion battery.